Livro didático, oralidade e podcast na formação de professores de língua portuguesa: ancoragens e deslocamentos - CRUZ, Mayara Alexandra Oliveira da (Universidade Federal do Pará, 2023)
The emergence and popularization of Digital Information and Communication Technologies (TDIC), consolidated by the advancement of Computer-Mediated Communication (CMC), led to the insertion of digital genres in Portuguese Language Textbooks (LDLP). In this direction, the research seeks to understand the didacticization of the digital discursive genre podcast in Portuguese language textbooks. Thus, the main objective of this study is to understand how Portuguese language teachers, working in the final years of Elementary School, in public schools, mobilize the digital podcast genre proposed in Portuguese language textbooks as a function of the teaching and learning process. This work is situated in the field of Teaching and Learning Languages and Cultures (EALC). The main scholars mobilized are Bakhtin (1997) and his Circle, Rojo (2012, 2015), Bunzen (2009) and Villarta-Neder and Ferreira (2020). The methodological approach is based on documental analysis of textbooks, used by public school teachers, as well as on collaborative research, considering the need for greater articulation between the university and the school. Regarding the treatment of the podcast in LDLP, there was an insufficient and superficial approach. It is noteworthy that, due to the pandemic context, it was necessary to hold online training meetings, in remote mode, with teachers from the final years of Elementary School, to generate data. The results reveal the presence of several oral genres in teaching practices, as well as digital tools and digital genres. However, such data also reveal that there are efforts to be undertaken regarding the understanding and more purposeful use of the textbook, the use of the podcast discursive genre in the classroom and teacher training focused on new technologies in favor of the teaching process. teaching and learning. In this sense, a didactic proposal about the podcast genre is presented, based on the accomplishment of a pedagogical work that expands and strengthens the students' competence for the increasingly effective use of digital and oral practices from a reflexive and contextualized systematization.